Food additives and bioactive substances from in vitro systems of edible plants from the Balkan peninsula. Issue 11 (28th August 2018) - Vrancheva, Radka; Ivanov, Ivan; Aneva, Ina; Stoyanova, Magdalena; Pavlov, Atanas
Abstract: During the last few years there is an increasing demand to the natural biologically active compounds. According to the World Health Organization (WHO) about 11% of the conventional medicines are of plant origin. Nowadays, plant biotechnologies are modern and reliable tool for producing valuable bioactive compounds. Recently, the potential of plant cells as foods also was confirmed. The advantages of plant in vitro systems over the intact plants are well known: growing under controlled and optimized laboratory conditions; independence of climatic and soil differences; preservation of rare and endangered plant species; cultivation in diverse bioreactor systems for increasing production yields of target metabolites. There have been developed many in vitro systems for production of various plant bioactive compounds with potential application in food industries. But potential for industrial implementation of this technology depends on solving problems with the scale‐up of bioreactor cultivation, development of additional approaches for improving/modification of bioactivities of the target plant secondary metabolites, and to find way to exclude or replace in the culture media the carcinogenic plant growth regulator 2, 4‐dichlorophenoxyacetic acid (2, 4‐D) with its safety analogs, such as α‐naphtaleneacetic acid (NAA) and/or indole‐3‐butyric acid (IBA). The aim of the current mini review is to summarize information about different in vitro systems of edible plants from the Balkan Peninsula with potential for producing food additives and biologically active substances and to describe prospects for successful industrial implementation of this technology.